The Actions of Centrally Administered Nesfatin-1 on Emesis, Feeding, and Locomotor Activity in Suncus murinus (House Musk Shrew) - Lu, Zengbing; Cui, Dexuan; Liu, Julia Yuen Hang; Jiang, Bin; Ngan, Man Piu; Sakata, Ichiro; Takemi, Shota; Sakai, Takafumi; Lin, Ge; Chan, Sze Wa; Rudd, John A. (Frontiers in Pharmacology, 2022)
Abstract Nesfatin-1 is an anorectic peptide expressed in both peripheral tissues and brain areas involved in the regulation of feeding, emotion and emesis. The aim of the present study is to characterize the distribution of NUCB2/nesfatin-1 in Suncus murinus and to investigate the actions of nesfatin-1 to affect gastrointestinal contractility, emesis, food and water intake, and locomotor activity. The deduced amino acid sequence of S. murinus nesfatin-1 using in silico cloning showed high homology with humans and rodents. NUCB2 mRNA was detected throughout the entire brain and in the gastrointestinal tract, including the stomach and gut. Western blot analysis and immunohistochemistry confirmed the expression of nesfatin-1 protein in these regions. The NUCB2 mRNA levels in the hypothalamus, hippocampus and brainstem were significantly decreased, whereas that in the striatum were increased after 24 h starvation compared to ad libitum-fed animals (P<0.05). In in vitro studies, nesfatin-1 (0.3 – 1000 pM) failed to contract or relax the isolated gastric antrum and intestinal segments. In conscious, freely moving animals, intracerebroventricular administration of nesfatin-1 (1 – 50 pmol) induced emesis (P<0.05) and suppressed 6-h cumulative food intake (P<0.05), without affecting the latency to feeding. Nesfatin-1 (25 pmol, i.c.v.) decreased 24-h cumulative food and water intake by 28.3% and 35.4%, respectively (P<0.01). No significant differences in locomotor activity were observed. In conclusion, NUCB2/nesfatin-1 might be a potent regulator of feeding and emesis in S. murinus. Further studies are required to elucidate the mechanism of actions of this peptide as a mediator linking the brainstem NUCB2/nesfatin-1 to forebrain system.